THE LEGALITY OF INTERFAITH MARRIAGE CONDUCTED ABROAD IN THE PERSPECTIVE OF INDONESIAN LAW - Anak Agung Istri Agung Nindasari Trisnawijayanti; Anak Agung Istri Ari Atu Dewi (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Based on the provisions of the legislation that applies positively in Indonesia, it is stated that interfaith marriages cannot be carried out. However, it turns out that interfaith marriages still occur as a result of social interaction among all Indonesian citizens, so the interfaith couples carry out their marriages abroad. Interfaith marriages are implicitly not specifically regulated in the Marriage Law. The problem studied in this paper is how the legality of interfaith marriages abroad in the perspective of Indonesian law. The purpose of this study is to find out the legality of interfaith marriages abroad in the perspective of Indonesian law. This research uses a normative method by reviewing the laws and regulations related to the legal issues under study. The results of the study concluded that the legitimacy of interfaith marriages outside the jurisdiction of Indonesia was invalid because it violated several articles in the Marriage Law. If interfaith marriages abroad still occur, then the marriage is a violation of the law.